WRITTEN CUED RETELL STRATEGY CAN IMPROVE STUDENTS’ WRITING SKILL AT THE EIGHTH GRADE STUDENTS OF SMPN 7 SURAKARTA - Setyoningsih, Lina (Widya Wacana: Jurnal Ilmiah, 2018)
ABSTRACTThis  research  concerned  on  improving  students’  writing  skill  using Written Cued Retell Strategy. The objectives of this research are as follows: 1) to know that Written Cued Retell Strategy can improve students’ writing skill at the eighth grade students of SMPN 7 Surakarta especially class 8G in academic year 2017/2018, and 2) to know how the implementation of Written Cued Retell Strategy at the eighth grade students of SMPN 7 Surakarta especially class 8G in academic year 2017/2018 is. In this research, the researcher used qualitative and quantitative methods. The qualitative method consisted of observation, interview, and documentation. While the quantitative method was calculating the mean score of pre test, post test 1 and 2, and t-test. The result of this research showed that Written Cued Retell Strategy could improve students’ writing skill in recount text at the eighth grade students of SMP N 7 Surakarta especially class 8G. The improvement could be seen from the result of the tests. The mean score of pre test was 54, post test 1 was 71,50, and post test 2 was 85,50. Based on the result of the analysis  using  t-test,  the  t-table  in  significance  5%=2.042  and  significance 1%=2.750. It could be concluded that t0 > tt in significance 5% and 1% (2.042 < 6.07  >  2.750).  It  meant  that  there  was  significant  improvement  in  students’ writing skill using Written Cued Retell Strategy in pre test and post tests. Keywords: Classroom Action Research, Students’ Writing Skill, Written CuedRetell Strategy. ABSTRAKPenelitian ini berkaitan dengan peningkatan keterampilan menulis siswa menggunakan Strategi Menceritakan Kembali Cued yang Ditulis. Tujuan dari penelitian ini adalah sebagai berikut: 1) untuk mengetahui bahwa Strategi Retell Cued Retell dapat meningkatkan keterampilan menulis siswa pada siswa kelas delapan SMPN 7 Surakarta khususnya kelas 8G pada tahun akademik 2017/2018, dan 2) untuk mengetahui bagaimana Implementasi Strategi Menceritakan Kembali Cued Tertulis pada siswa kelas delapan SMPN 7 Surakarta khususnya kelas 8G pada tahun akademik 2017/2018 adalah. Dalam penelitian ini, peneliti menggunakan metode kualitatif dan kuantitatif. Metode kualitatif terdiri dari observasi, wawancara, dan dokumentasi. Sedangkan metode kuantitatif menghitung skor rata-rata pre test, post test 1 dan 2, dan t-test. Hasil penelitian ini menunjukkan bahwa Strategi Menulis Kembali Cued dapat meningkatkan keterampilan menulis siswa dalam teks recount pada siswa kelas delapan SMP N 7 Surakarta khususnya kelas 8G. Peningkatan itu bisa dilihat dari hasil tes. Nilai rata-rata pre tes adalah 54, post test 1 adalah 71,50, dan post test 2 adalah 85,50. Berdasarkan hasil analisis menggunakan uji-t, t-tabel signifikansi 5% = 2,042 dan signifikansi 1% = 2,750. Dapat disimpulkan bahwa t0> tt signifikansi 5% dan 1% (2,042 <6,07> 2,750). Ini berarti bahwa ada peningkatan yang signifikan dalam keterampilan menulis siswa menggunakan Strategi Menceritakan Kembali Cued Tertulis dalam tes awal dan post tes. Kata kunci: Penelitian Tindakan Kelas, Keterampilan Menulis Siswa, Cued TertulisMenceritakan kembali strategi.